Pengaruh Investasi, Inflasi dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Yuni Maulida; Abdul Hamid; Faisal Umardani Hasibuan (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2022)
This study aims to determine the effect of investment, inflation and human development index on economic growth in Aceh Province. The research method used is a quantitative method using secondary data from 2006-2020. Data analysis used multiple linear regression equation, t test, F test and coefficient of determination test (R2). The results of the multiple linear regression equation test show that investment has a negative effect on economic growth, inflation and the human development index have a positive effect on economic growth. The results of the t-test of the investment variable t sig > 5% (0.0213 > 0.05) can be stated that investment has a not significant effect on economic growth, the inflation variable t sig > 5% (0.484 > 0.05) can be stated that inflation has a not significant effect on economic growth . The human development index variable t sig < 5% (0.001 <0.05) can be stated that the human development index has a significant effect on economic growth. The results of the F F test sig < 5% (0.023 <0.05) can be stated simultaneously that investment, inflation and human development index have a significant effect on economic growth in Aceh Province. The test results of the coefficient of determination (R2) obtained 0.895 or 89.5% investment, inflation and human development index can explain the variable economic growth.